Molecular identification of thermophilic bacteria with antimicrobial activity isolated from hot springs in North Sumatra, Indonesia - CHRISMIS NOVALINDA GINTING; FINNA PISKA; HARMILENI HARMILENI; EDY FACHRIAL (Society for Indonesian Biodiversity, 2023)
Abstract. Ginting CN, Piska F, Harmileni, Fachrial E. 2023. Molecular identification of thermophilic bacteria with antimicrobial activity isolated from hot springs in North Sumatra, Indonesia. Biodiversitas 24: 752-758. Microorganisms such as thermophilic bacteria are promising sources of antimicrobial compounds due to their abundance, which has yet to be widely investigated. Therefore, this study aims to identify thermophilic bacteria isolated from natural hot springs, Sidebuk Debuk, in North Sumatra, Indonesia. The bacteria were isolated from sediments and hot springs water. Isolated 10 bacteria were characterized and identified based on their morphological and biochemical properties, which included gelatinase activity, motility, citrate utilization, triple sugar iron agar test, catalase test, cell shape, color, and Gram staining. Antimicrobial activity was tested using the disc diffusion method against Escherichia coli and Staphylococcus aureus. The most potential isolates were identified molecularly by amplification of 16S rRNA genes using universal primers. The sequences result were trimmed and assembled using BioEdit and submitted to BLAST to determine the homology of the bacteria. The isolate ITU9 was identified as Bacillus megaterium and exhibited the best antimicrobial activity with an inhibition zone of 9.5 mm against S. aureus during 72 h of incubation. This research showed that the thermophilic B. megaterium strain ITU9 was successfully isolated from Sidebuk Debuk hot springs and had stable antimicrobial activity for 72 h against E. coli and S. aureus.